THE EFFECTIVENESS OF USING THE PROBLEM BASED LEARNING (PBL) LEARNING MODEL ON THE CRITICAL THINKING ABILITY OF STUDENTS IN ISLAMIC CULTURAL HISTORY LESSONS - Bariyah, Eva Musthofatul (JPGI (Jurnal Penelitian Guru Indonesia), 2023)
Learning the subject of Islamic Cultural History (SKI) directs students to understand and criticize the historical traces of Islamic civilization. For this reason, appropriate learning is needed so that learning objectives are achieved optimally. This study attempts to describe the correlation of the use of the Problem Based Learning (PBL) learning model on students' critical thinking skills in SKI subjects. The researcher uses primary data, namely using the critical thinking ability score data of the students who are the samples of this study. The method used is the evaluation method and the comparative method. In this case, comparing the scores of critical thinking skills before and after using the PBL Learning Model. The results of this study indicate that there are significant differences in critical thinking ability scores before and after using the PBL Learning Model. There is also a very strong correlation between the use of the PBL Learning Model and critical thinking skills. It can also be stated that the PBL Learning Model is effectively used to improve students' critical thinking skills in SKI subjects.